Municipal Waste Management: Case Study of Recycling in Pelotas, RS - Godecke, Marcos Vinicius; Walerko, Vandressa Siqueira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Confronted with evidence related to the low rate of recycling in Brazil, this study takes the case of Pelotas, south of the state of Rio Grande do Sul, to discuss programs that can be implemented for increasing the efficiency of municipal collection of household recyclables. In addition to bibliographic and documentary references, uses field research and interviews with key stakeholders, including municipal technicians, recycling cooperatives and the population who use the service. As a result two programs are proposed: the extension of the agreement with the recycling cooperatives, enabling them to collect door-to-door recyclable, and environmental education of the population, aimed at raising the level of recyclables segregation in households.